THE PSYCHO-SEMANTIC APPROACHES ?? INTERPERSONAL RELATIONSHIPS - Begoyan, A. (Main Issues Of Pedagogy And Psychology, 2017)
The article presents a psychosemantic approach to interpersonal relations, which is based on the theoretical concepts of O. Harvey, D. Hunt, & H. Schroeder, as well as, L.Vygotski, A. N. Leontev, D.N. Leontev, V. Nalimov, and others. A psychosemantic approach to interpersonal relations manifests through the concepts of person’s conceptual system, gestalt-concepts, conceptual dissonance, common conceptual space, and conceptual flexibility. The main pathogenic strategies of conceptual dissonance smoothing, like distortion of existing reality, distortion of the laws and principles offormal logic, and rejection of previous experience, are also discussed.